Effect of warfarin anticoagulation on thrombin generation in patients with idiopathic pulmonary arterial hypertension - Jansa, Pavel; Hrachovinová, Ingrid; Ambrož, David; Marešová, Jana; Poláček, Pavel; Šimková, Iveta; Linhart, Aleš; Aschermann, Michael (Bratislavské lekárske listy, 2010)
BACKGROUND: Oral anticoagulant therapy is recommended for patients with pulmonary arterial hypertension (PAH). The rationale for the use of anticoagulant treatment is based on thrombophylic predisposition in PAH and improvement of survival in patients treated with anticoagulation. However, the target INR value has not been evaluated. The aim of this study was to analyze thrombin generation in patients with PAH treated with warfarin anticoagulation. METHODS: The study was performed in 58 patients with idiopathic PAH treated with warfarin at stable doses. Thrombin generation assay was performed in all subjects and three parameters were derived from the thrombin generation curves: lag time, maximal concentration of formed thrombin (peak thrombin) and area under the curve (AUC). Thrombin generation parameters were correlated with INR and compared between the patient groups with different intensity of anticoagulant therapy. RESULTS: Significant correlation between the lag time and INR was observed (r = 0.495, p < 0.001). Significant negative correlation between the maximal concentration of formed thrombin and INR and between the area under the curve of thrombin generation and INR was observed (r = -0.709, p < 0.001 and r = -0.784, p < 0.001, respectively). Thrombin generation was significantly reduced in patients with INR between 1.5 and 2.5. CONCLUSIONS: Low-intensity warfarin anticoagulation with target INR between 1.5 and 2.5 could be effective and sufficient to suppress thrombin generation in patients with idiopathic PAH (Fig. 3, Tab. 4, Ref. 12). Full Text in free PDF www.bmj.sk.
Keywords: Anticoagulants; antikoagulancia; plicní hypertenze; lidé středního věku; lidé; Female; mužské pohlaví; INR; trombin; International Normalized Ratio; Male; Hypertension, Pulmonary; Middle Aged; Thrombin; ženské pohlaví; Humans